Salivary bypass tube in managing persistent and large pharyngocutaneous and tracheoesophageal fistulas: a series of seven cases - Nurul Najwa Mohd Zakir; Zulkifli Yusof; Irfan Mohamad (The Egyptian Journal of Otolaryngology, 2023)
Abstract Background A salivary bypass tube (SBT) is a silicone tube that directs oral content from the mouth to the esophagus. We studied a series of seven cases of persistent and large neck fistulas of different aetiologies to assess the beneficial use of SBTs in each case. Case presentation A total of seven patients underwent SBT insertion, six cases were post-total laryngectomy with underlying laryngeal malignancy, and one case was poor wound healing of a neck abscess after extensive drainage. Five cases have pharyngocutaneous fistula (PCF) and two cases have tracheoesophageal fistula (TEF), and all of the cases have failed conservative and multiple surgical management for fistula closure, with some concurrently having neopharynx stenosis. Post-insertion, all patients were able to eat orally after day 2 to 1-week. The duration of tube usage was one month in the three cases of persistent PCF post-operatively, and in two cases, the fistula was healed and the tube was removed without fistula recurrence. The other four cases (three post-radiotherapy fistulas and one stoma recurrence) were planned for lifelong use, with the duration of usage ranging from 4 months to 3 years. The outcome is their fistula is dry, and they tolerate the tube well. There were no intraoperative or immediate postoperative complications, and no complications were observed in the temporary usage cases. Among the patients who had to use the tube for a longer term, one had localised pressure necrosis of regional soft tissue that resolved after tube adjustment, and another had a loose-fitting tube that displaced distally into the oesophagus and resolved with a larger tube. Conclusions SBT is safe, easy-to-apply, reduces morbidity, improves mental health, reduces inpatient stay, and overall improves the patient's quality of life in the management of persistent and large TEF and PCF for temporary or long-term usage.